Thermal Decomposition of Donor‐Stabilized Phosphinoborane PH2BH2NMe3: A Tensimetry Study. Issue 35 (9th September 2019) - Butlak, Alina V.; Kazakov, Igor V.; Stauber, Andreas; Hegen, Oliver; Scheer, Manfred; Pomogaeva, Anna V.; Timoshkin, Alexey Y.
Abstract : The thermal decomposition of PH2 BH2 · NMe3 (1 ) in closed system was studied by static tensimetry with membrane null‐manometer. Compound1 is unstable already at room temperature and partially decomposes with the release of gaseous trimethylamine and nonvolatile polymeric material. Storage of1 at 311 K for 53 days results in evolution of small amounts of hydrogen and phosphine. At temperatures up to 329 K, PH3 evolution and BH3 NMe3 adduct formation is observed after 3 days, and above 387 K, considerable amount of hydrogen gas is released. The data obtained indicate that the pyrolysis of1 in the closed system may result in the enrichment of the condensed phase with boron due to phosphine loss. Abstract : Thermal decomposition of the title compound in a closed system in the temperature range 298–568 K was studied by vapor pressure measurements. At temperatures below 329 K, NMe3, PH3, BH3 NMe3, and polymers are formed as primary decomposition products. Noticeable dihydrogen evolution starts above 387 K. Due to phosphine loss, upon decomposition the condensed phase is enriched with boron.